Clinical and Epidemiological Aspectsin Indigenous Elderly People with Tuberculosis in a State in the Brazilian Amazon - Viviane Ferraz Ferreira de Aguiar; Dayara de Nazaré Rosa de Carvalho; Marcela Raíssa Asevedo Dergan; Dandara de Fátima Ribeiro Bendelaque; Thiago Augusto Ferreira dos Anjos; Simone Aguiar da Silva Figueira; Ivonete Vieira Pereira Peixoto; Fabiana de Souza Orlandi (Archives of Current Research International, 2023)
Objective: To analyze the clinical and epidemiological aspects of tuberculosis among indigenous elderly individuals in Pará, from 2010 to 2019. Methodology: This study employed an epidemiological, quantitative approach using data from the Information System for Notifiable Diseases. The data comprised new cases of tuberculosis reported in elderly individuals in the state of Pará between 2010 and 2019. The data, publicly accessible and stored in epidemiological indicators of tuberculosis in the health macro-regions of Pará, were analyzed using descriptive statistics in Microsoft Excel© software. The results were presented through graphs and tables, displaying the absolute and percentage frequency distribution of the selected variables. Results and Discussion: A total of 99 cases were identified. The year with the highest occurrence of cases was 2016, with 14 cases (14.14%) reported. The majority of cases were incident in females, with 51 cases (51.52%). The most affected age group was between 70 and 79 years old, accounting for 45 cases (45.45%). Among individuals with no schooling, there was a higher prevalence of illiterate elderly people, with 59 cases (59.60%). Conclusion: The relationship between TB cases in indigenous elderly individuals and social determinants such as health conditions, housing, and education is highlighted to demonstrate that social inequality among different socioeconomic classes affects the health-disease process.